Cost optimization for the 100% renewable electricity scenario for the Java-Bali grid - Matthias Günther; Michael Eichinger (Center of Biomass & Renewable Energy, Diponegoro University, 2018)
A 100% renewable electricity supply is no insurmountable technical problem anymore after the respective technologies to harvest the energy from multiple renewable energy sources have been developed and have reached a high level of maturity. A problem may rather be suspected to reside on the economic side of an exclusively renewable electricity supply. The present study examines the economic implications of a renewable energy scenario for the Java-Bali grid. Based on given energy supply scenarios, the costs of an electricity supply from renewable energy sources alone are determined. Economic optimum configurations are determined for which the annual system costs and accordingly the power generation costs are minimized. First the system running costs are considered, i.e. the operation and maintenance costs as well as the costs of the continuous renovation of system components, while capital costs are not taken into account. After this the capital costs are taken into consideration, and total system costs and power generation costs are determined. The main result is a specification of economic optimum system configurations. One important result is that a future electricity supply from renewable resources alone is not more expensive than the current power generation in developed countries. Another result is that the integration of special long-term storage into the Java-Bali grid, like for instance methane storages, besides pumped storages and batteries, is not economically favourable if further moderate battery cost reductions are reached.Article History: Received May 18th 2018; Received in revised form August 16th 2018; Accepted October 1st 2018; Available onlineHow to Cite This Article: Günther, M., Eichinger, M., (2018) Cost Optimization for the 100% Renewable Electricity Scenario for the Java-Bali Grid, International Journal of Renewable Energi Development, 7(3), 269-276.https://doi.org/10.14710/ijred.7.3.269-276